Continuity at the Two Poles of Everyday Life Sociology: Henri Lefebvre in the Footnote of Michel De Certeau - Mustafa Ertürk (İstanbul Üniversitesi Sosyoloji Dergisi)
Henri Lefebvre’s and Michel de Certeau’s approaches to everyday life continue to remain the two most dominant paradigms in today’s social sciences. As two distinguished figures of everyday life sociology, Lefebvre’s and de Certeau’s methodological tools, sources, and intellectual backgrounds as well as the scope they purposed to reach differ from each other. Despite all these differences, the area where their long-term conceptualizations of everyday-life theory intersect offers an opportunity to frame an important perspective on everyday life sociology. De Certeau, who significantly benefitted from Lefebvre, only mentioned Lefebvre once in a footnote on his study of everyday life, a footnote that makes up the starting point of this study. By drawing from this footnote, studying the everyday life works of two thinkers together conspicuously allows the everyday life critiques of Lefebvre to be traced in de Certeau’s everyday life theory. This study is an attempt to study the everyday life approaches of both thinkers together beyond an eclectic adaptation of the theories of Lefebvre and de Certeau and follows the continuity of the ways the two thinkers problematized everyday life using their conceptual trajectory.